Tolerance in Islam: Guard Peace and Respecting Differences - Darmawanita Darmawanita (Inspire Global Insight Journal, 2026)
Tolerance in Islam is a fundamental principle that supports social harmony amidst a diverse society. Islam teaches mutual respect, maintaining peace, and accepting differences as part of social life. This study aims to examine the principles of tolerance in Islam based on the teachings of the Qur'an and Hadith and how they are implemented in social life. The research method used is a literature review with a qualitative descriptive approach. The results show that Islam emphasizes tolerance in various aspects life, good in social interactions and in religious context. In conclusion, Islamic teachings on tolerance play a vital role in building a harmonious and peaceful society.